Human enhancement and factor X - Simonstein, F. (Journal of medical ethics, 2008)
During the last congress of the International Association of Bioethics in Beijing, there was a special session on human enhancement. John Harris, pioneer in the discussions on the ethics of enhancement,1 summarised this session, describing the focus of different panelists.2 This session included:Biopsychological enhancements (Julian Savulescu)The possibility of regulating emotions through pharmacological means (S. Matthew Liao)Biases that may affect our judgments against human enhancement (Nick Bostronm)Health care inequalities that will follow from the adoption of genetic technology (Claudio Tamburrini)Social impact and costs of adopting the new technology (Anders Sandberg)A discussion on women enhancing their physical strength as men through genetic modification (Torbjorn Tannsjo and Claudio Tamburrini).The Beijing panel did not address women’s (necessary!) involvement in the enhancement scenario. Of course, not every aspect of a topic can be covered in one session of a congress and some aspects may remain unaddressed; mainly, because these sessions draw from the research interests of the presenters. However, neither John Harris nor Julian Savulescu (the chair of this session) has yet addressed women’s crucial involvement in the enhancement scenario. It is the aim of this paper to draw attention to the invisibility of the ‘vessel’ in these discussions. Enhancement may be justified; but clearly, it will also affect women. In this scenario, will women be worse off?Firstly, I would like to point out that I believe that enhancement may be a necessary step in the future of human evolution. As I have explained elsewhere,3 health care systems in the developed world are near to collapse under the pressure of late onset chronic diseases. Largely successful in preventing early deaths in the last century, health care systems have prompted a new plague, recognised lately by the World Health Organization (WHO) as a new pandemic …